Peningkatan Nilai Produk Melalui Inovasi Kemasan pada UMKM Rengginang Singkong “Presida” Desa Ellak Daya, Kec. Lenteng, Kab. Sumenep - Siti Novita Asti; Dewi Wulansari; Wasil Afandi; Viona, Viona; Rafikatul Lisyana Mashudah; Rifki Adi Rahman; Erik Putra Sadaliya; Tolak Iyam (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in driving local economic growth. "Presida" MSME, which produces cassava-based rengginang in Ellak Daya Village, Sumenep, faces challenges related to its simple and visually unappealing product packaging. This article aims to enhance product value through packaging innovation that is more functional, aesthetic, and aligned with market trends. The program was implemented in three stages: preparation, implementation, and monitoring and evaluation. A participatory approach was adopted to actively involve partners in training and designing the new packaging. The results indicate improved partner understanding of the importance of packaging and successful adoption of a more appealing and practical design. This packaging innovation contributes to increased product competitiveness and market expansion potential for the "Presida" MSME.